A deep look into the storm: Israeli multi-center experience of coronavirus disease 2019 (COVID-19) in patients with autoimmune inflammatory rheumatic diseases before and after vaccinations - Kharouf, Fadi; Eviatar, Tali; Braun, Maya; Pokroy-Shapira, Elisheva; Brodavka, Michal; Zloof, Yair; Agmon-Levin, Nancy; Toledano, Kochava; Oren, Shirly; Lidar, Merav; Zisman, Devy; Tavor, Yonit; et al. (Frontiers in Immunology, 2023)
Objective: We aimed to characterize the course of COVID-19 in autoimmune inflammatory rheumatic disease (AIIRD) patients in Israel, taking into consideration several remarkable aspects, including the outcomes of the different outbreaks, the effect of vaccination campaigns, and AIIRD activity post-recovery. Methods: We established a national registry of AIIRD patients diagnosed with COVID-19, including demographic data, AIIRD diagnosis, duration and systemic involvement, comorbidities, date of COVID-19 diagnosis, clinical course, and dates of vaccinations. COVID-19 was diagnosed by a positive SARS-CoV-2 polymerase chain reaction. Results: Israel experienced 4 outbreaks of COVID-19 until 30.11.2021. The first three outbreaks (1.3.2020 – 30.4.2021) comprised 298 AIIRD patients. 64.9% had a mild disease and 24.2% had a severe course; 161 (53.3%) patients were hospitalized, 27 (8.9%) died. The 4th outbreak (delta variant), starting 6 months after the beginning of the vaccination campaign comprised 110 patients. Despite similar demographic and clinical characteristics, a smaller proportion of AIIRD patients had negative outcomes as compared to the first 3 outbreaks, with regards to severity (16 patients,14.5%), hospitalization (29 patients, 26.4%) and death (7 patients, 6.4%). COVID-19 did not seem to influence the AIIRD activity 1-3 months post-recovery. Conclusions: COVID-19 is more severe and has an increased mortality in active AIIRD patients with systemic involvement, older age and comorbidities. Vaccination with 3 doses of the mRNA vaccine against SARS-CoV-2 protected from severe COVID-19, hospitalization and death during the 4th outbreak. The pattern of spread of COVID-19 in AIIRD patients was similar to the general population.